Protocolo de assistência de enfermagem para pacientes submetidos a transplante cardíaco internados em unidade de terapia intensiva - GONÇALVES, Glória Letícia Oliveira (2019)
The cardiac transplantation is a therapeutic modality proven in cardiac patients in end-stage. Currently, are the best therapeutic option and the last therapy for heart failure patients in endstage. The intention of cardiac transplants is extends the life of this patient affected by the disease that focused on heart, significantly changing his/her life. This study aims to develop a protocol for nursing care for the transplanted heart in Intensive Care Unit. It is characterized by being descriptive and qualitative approach realized through literature search between 2000 and 2010. It presents, in details, the technical implementation procedures such as, the topic selection of the topic to be researched, the formulation of the problems and objectives, reading and analyzing bibliographies, among others. It considers as probable nursing diagnosis identified in postoperative patients after cardiac surgery, the following: risk for impaired skin integrity; ineffective breathing pattern; infection risk; acute pain. Such diagnoses, as well as others, are accompanied by their defining characteristics, risk factors and nursing interventions. It proposes as main procedures done with patient in postoperative of cardiac surgery, the following: cardiac monitoring, water balance, curative cares, bed bathes, among others. It is believed in the importance of the protocol as allied to the information of the procedures necessary to take care of the patient hospitalized in UTI due to the cardiac transplantation, since the demonstration of the main diagnoses and nursing interventions are implemented in themselves will help the development of strategies to become easier the nursing care. It contributes to the nursing professionals can acquire more knowledge and reflects on the care provided to patient, to promote a systematic care, humanized and with quality.